2021
DOI: 10.3389/fgene.2021.756172
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Divergence in Transmitted SNPs of DNA Replication/Transcription and Their Impact on Gene Expression in Polyploid Brassica napus

Abstract: The marked increase in plant genomic data has provided valuable resources for investigating the dynamic evolution of duplicate genes in polyploidy. Brassica napus is an ideal model species for investigating polyploid genome evolution. The present study comprehensively analyzed DNA and RNA variation of two representative B. napus inbredlines, Zhongshuang11 and Zhongyou821, and we investigated gene expression levels of An and Cn subgenomes in multiple tissues of the two lines. The distribution of transmitted sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In this context, it would be interesting to explore whether the expression level of candidate TFs differs between homologous genes. Alongside that, previous studies also found that the gene expression shifts in the polyploid progeny were related to transposable elements [21] and SNPs [22], etc.…”
Section: Introductionmentioning
confidence: 87%
“…In this context, it would be interesting to explore whether the expression level of candidate TFs differs between homologous genes. Alongside that, previous studies also found that the gene expression shifts in the polyploid progeny were related to transposable elements [21] and SNPs [22], etc.…”
Section: Introductionmentioning
confidence: 87%